Effect of Betulinic Acid on Lipid Homeostasis and Atherosclerotic Index - Afghan, Sher (International Journal of Pathology, 2022)
Introduction: Dysregulation in lipid metabolism and inflammatory response triggering lipid oxidation results in hyperlipidemia and induces the progression of atherosclerotic cardiovascular disease. Betulinic acid possesses lipid lowering and anti-inflammatory properties, therefore it may play an important role in athero-sclerosis prevention and Lipid homeostasis.Material &Methods: An experimental study was conducted at the campus of Northwest school of medicine, Hayatabad for a period of two months from 1st Dec 2021 – 3rd Feb 2022. A sample of 30 male BALB/c mice was divided into three groups. Group I was the negative control that received normal food and water for a period of 42 days. Group II was positive control given a diet high in fat content. Group III was also given diet high in fat content and betulinic acid in a dose of 10mg/kg.Results: The serum TG level (mg/kg) of group II was 202.3 + 28, VLDL (mg/kg) was 40.2 + 5.7, TC (mg/kg) was 205.6 + 51.8, LD (mg/kg) was 40.5 + 5.9 and HDL (mg/kg) was 29.4 + 5.6. AI was calculated to be 0.47 + 0.09. Betulinic acid group showed a TG level of 120.7 + 29.3, VLDL of 34.1 + 9.3, TC of 152.7 + 40.9, LDL of 33.8 + 8.7 and HDL of 49.3 + 3.4. AI for group III was 0.02 + 0.07. Between group II & III, Paired sample t test showed a significant difference of 0.00 in TG levels, 0.04 for VLDL level, 0.4 for total cholesterol, 0.03 for LDL and 0.00 for HDL. The atherogenic index also showed a statistically significant P value of <0.05 Conclusion: Our findings suggest a significant protective effect of BA in cardiovascular and atherosclerotic diseases. It not only reduces LDL, VLDL, TG and cholesterol levels, reducing the atherogenic index, but also raised the serum HDL levels.